Process-Parameter-Dependent Structural, Electrical, and Optical Properties of Reactive Magnetron Sputtered Ag-Cu-O Films - P. Narayana Reddy; A. Sreedhar; M. Hari Prasad Reddy; S. Uthanna; J. F. Pierson (Journal of Nanotechnology)
Silver-copper-oxide thin films were formed by RF magnetron sputtering technique using Ag80Cu20 target at various oxygen partial pressures in the range 5 × 10−3–8 ×10−2 Pa and substrate temperatures in the range 303–523 K. The effect of oxygen partial pressure and substrate temperature on the structure and surface morphology and electrical and optical properties of the films were studied. The Ag-Cu-O films formed at room temperature (303 K) and at low oxygen partial pressure of 5 × 10−3 Pa were mixed phase of Ag2Cu2O3 and Ag, while those deposited at 2 × 10−2 Pa were composed of Ag2Cu2O4 and Ag2Cu2O3 phases. The crystallinity of the films formed at oxygen partial pressure of 2 × 10−2 Pa increased with the increase of substrate temperature from 303 to 423 K. Further increase of substrate temperature to 523 K, the films were decomposed in to Ag2O and Ag phases. The electrical resistivity of the films decreased from 0.8 Ωcm with the increase of substrate temperature from 303 to 473 K due to improvement in the crystallinity of the phase. The optical band gap of the Ag-Cu-O films increased from 1.47 to 1.83 eV with the increase of substrate temperature from 303 to 473 K.